VELOCIDADE DE CRESCIMENTO DE Trichoderma ISOLADOS DE Sclerotium rolfsii - COSTA, Brenda Fernandes,; PESSÔA, Guilherme Martins,; SANTOS, Stephany,; BLANCO, Neder Henrique Martinez,; GRAICHEN, Felipe André Sganzerla, (ANAIS DO ENIC, 2023)
-